Induction of inflammatory responses from THP-1 cells by cell-free filtrates from clinical isolates of Alloiococcus otitidis. Issue 3 (April 2014) - Ashhurst-Smith, Christopher; Hall, Sharron T; Burns, Christine J; Stuart, John; Blackwell, C Caroline
In our model system using the THP-1 monocytic cell line, whole heat-killed cells of Alloiococcus otitidis elicited several pro-inflammatory cytokines identified in ear effusions of children with otitis media (OM). Levels of these cytokines were equivalent to or greater than those elicited by a standard Gram-positive otopathogen, Streptococcus pneumoniae . The current study examined the hypothesis that extracellular material produced by A. otitidis might also contribute to the inflammatory responses in OM. Cell-free culture filtrates of recent A. otitidis isolates ( n = 39) were tested for induction of pro-inflammatory cytokines from THP-1 cells primed with IFN-γ. The highest responses were from IL-8 followed by IL-1β, and the lowest from IL-6. Filtrates from nine isolates were treated with lysozyme or proteinase K to assess the nature of the extracellular stimulants. Peptidoglycan was not a major component eliciting the responses. There was no correlation between colony type or β-haemolysin production. Proteinase K treatment indicated extracellular proteins might induce the inflammatory responses, particularly the 70–75 ku band. Further studies on the role of the extracellular proteins of A. otitidis and cytokine responses in pathogenesis of ear infections are needed.